Induced calving in beef cattle - D.G. Morrison; G.H. Kiracofe; G. Jr. Heersche; R.R. Schalles; M. McKee (Kansas Agricultural Experiment Station Research Reports, 1975)
Calving was induced in 44 Polled Hereford cows at 275 days' gestation. Twenty mgs. Of dexamethasone (Azium) given intramuscularly caused parturition an average of 43.1 hours after injection (range 21 to 57). An injection of 30 mgs. Of prostaglandin F2 40 hours after dexamethasone effectively increased predictability of calving. Seven of nine cows calved 2.5 to five hours post prostaglandin (average time of calving 44.9 hours after dexamethasone). Prostaglandin given 30 hours after dexamethasone or dexamethasone 40 hours after prostaglandin was less effective ( average 46.6, range 34.5 to 57.5; average 75.3, range 63 to 100, respectively).
Keywords: Cattlemen& #x27; s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Dexamethasone; Prostaglandin; Production